Specific Features of Assessing Finance Efficiency of Deals on Russian M & A Market - E. M. Petrikova (Plekhanov Russian University of Economics, 2019)
Today M & A deals are still acute for Russia because of the necessity to search for additional sources of finance on Russian market of capital, raising finance stability and sustainability of Russian economy and finance market. The article studies problems dealing with assessment of finance efficiency of M & A deals, identifies key factors of the efficiency of M & A deals' mechanism in case of public companies-buyers and designed recommendations aimed at raising effectiveness of M & A mechanism on market. Apart from that the authors showed advantages and drawbacks of each method of financing M & A deals and put forward methodology of assessing and the calculation model for estimating finance efficiency of different ways of financing M & A deals and provided recommendations for choosing methods of financing on the basis of multiplayer selection substantiation within the frames of the calculation model designed by the authors. The use of this model was tested by its calculation for two M & A deals made in 2018.